Study of the Effective Factors in Women's Decision to Make Abortion and Their Belief and Religious Views in this Regard - Morteza Abdoljabbari; Marzieh Karamkhani; Nasrin Saharkhiz; Mohammadamin Pourhosseingholi; Masoumeh Shokri Khoubestani (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here Background and Objectives: As far as medical science is concerned, abortion is classified into four categories: spontaneous, induced, traumatic, and criminal. In spite of increase in the quantity and quality of contraceptive techniques and the rising level of public awareness of this issue, unwanted pregnancy is still a problem. When women face unwanted pregnancy, they might resort to criminal abortion. Materials and Methods: This is a descriptive research study. Researcher-made questionnaires were given to women with a history of abortion in the last 10 years, referring to health centers selected by Shahid Beheshti University of Medical Sciences. 369 subjects were randomly selected. The results were analyzed using the statistical software SPSS(Version 17). Results: The results of the study indicated that 26% of women were aged 26, and the educational level of 41.8% of them was diploma at the time of abortion.  Financial and family problems accounted for 20% and 15% of abortions respectively, and were the most prevalent factors. Spouses were the most influential encouraging factor in about 50% of the units under investigation. 29% and 17.5% of abortions were committed at 8th and 7th weeks of pregnancy respectively. 42.4% of individuals considered abortion as a religiously prohibited action and only 4.3% women having abortion did pay for their child's blood money. and viral diseases accounted for the reasons of abortion by 19.5 percent and 3.6 percent of women respectively. As for encouragement for abortion, the frequency distribution of the subjects revealed that 55.3 percent of women had abortion at the suggestion of their husbands and 0.3 percent did it due to their working conditions and because of others. The results of the study show that only 4.3 percent of women having abortion did pay for their child's blood money. Conclusion: Abortion is a controversial issue, which can be considered as a social or jurisprudence-associated issue; thus, it is necessary to take it into serious consideration in the Iranian-Islamic society.  Results of this study indicated the financial problem as the most prevalent factor and spouse's opinion as the most encouraging factor. Additionally, individuals had a frail attitude and ideology towards abortion. Keywords: Abortion, Intentional abortion, Women,Religious, Legal For downloading the full-text of this article please click here